Upaya Meningkatkan Keterampilan Berbicara Anak Melalui Media Kartu Gambar Pada Anak Kelompok A Di TK Islam Mardisiwi Surakarta Tahun Ajaran 2014/ 2015 - Sholihah, Umi, Ilham Sunaryo, M.Pd.AUD (2015)
The media card image is a media image that is pratical and attractive to be used for teachers in school teaching kindergarten children to develop speaking skills. Children's speaking skill is the basis to establish communication or reciprocal relationship with the people around him. Speaking skill also plays an important role, because speech is the basis for developing other capabilities. Media card image is suitable for storytelling learning in early childhood because this medium can teach children to speak. The purpose of this study was to determine the increase conversational skills in group A of children in kindergarten Islam Mardisiwi through the media card image. This study used a Classroom Action Research, research subjects and informants in this study were teachers and students in A group kindergarten Islam Mardisiwi of Surakarta academic year 2014/2015. Methods of data collection was done by observation and documentation. comparative analysis technique compared the ability of children of achievement or performance. The result showed that the speaking skills of children before the procedure until the second cycle increase. Before action, the pecycle was 36,80%, the firs cycle increased by 60% and second cycle reached 84,71%. The conclucion of this study was an increase of the speaking skills of children through the media card image in A group of children in kindergarten Islam Mardisiwi of Surakarta academic year 2014/2015.